Quality profile of fruit pulps commercialized in the municipality of Limoeiro do Norte, Ceará State, Brazil (Research, Society and Development, 2020)
The consumption of processed fruits increased, mainly due to the constant search for healthy food and the advancement in food technology. Thus, it is of great importance to assess the quality of these products, which must meet consumer requirements and current legislation. The present study aimed to evaluate the microbiological, physical-chemical and microscopic quality of frozen pulps of acerola, cajá, cashew and passion fruit marketed in the municipality of Limoeiro do Norte - CE. Were realized microbiological analyzes (counting of total and thermotolerant coliforms, counting of molds and yeasts and research of Salmonella sp.), physical-chemical analyzes (titratable acidity, pH, soluble solids, ratio and vitamin C) and microscopic analysis to detect foreign matter. According to the analyzes carried out, it was concluded that the fruit pulp samples analyzed were satisfactory in terms of Termotolerant Coliforms and Salmonella sp., indicative of adequate hygienic-sanitary conditions. For mold and yeast counting, only one brand presented 100% of the samples in compliance with the legislation. As for the physical-chemical parameters evaluated, only the samples of acerola pulp were adequate in terms of the required quality standards. It was possible to detect foreign matter, including the presence of dirt and insect parts. How many years of physical and chemical parameters, just as proven by steel pulp, will be presented, how many of the required standards of quality are required. It is possible to carry out the detection of material from abroad, within the presence of subjects and parts of insects.